2003
DOI: 10.1016/s0044-8486(03)00125-x
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic effects on precocious maturation, growth and smoltification in Atlantic salmon, Salmo salar

Abstract: Current Atlantic salmon farming practice induces early smoltification with artificial photoperiod regimes, however the importance of these photoperiods on parr maturation and interactions with smoltification are poorly understood. These questions were addressed in the present investigation, which examined the effects of photoperiod manipulation on the development, maturation and smoltification of individually tagged parr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 51 publications
2
30
0
Order By: Relevance
“…Furthermore, Thorpe (1994) has suggested that the initiation of maturation could be influenced prior to first feeding. Similarly, Berrill et al (2003) found that an 8 week period of short days (LD10:14) applied in May, shortly after first feeding in March, increased maturation rates compared to similar regimes applied later in the summer, highlighting a specific period of sensitivity in early development.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Furthermore, Thorpe (1994) has suggested that the initiation of maturation could be influenced prior to first feeding. Similarly, Berrill et al (2003) found that an 8 week period of short days (LD10:14) applied in May, shortly after first feeding in March, increased maturation rates compared to similar regimes applied later in the summer, highlighting a specific period of sensitivity in early development.…”
Section: Introductionmentioning
confidence: 84%
“…Consequently, the current study leads on from that of Berrill et al (2003) and aims to investigate the importance of the timing and duration of short day photoperiod regimes during a proposed sensitive period in early development. In order to achieve this 8 and 12 week periods of short days were applied at two times from shortly after first feeding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With freshwater trout, experimental modification of the seasonally-varying cycle of day length has been used for the production of year-round supplies of eggs for commercial fish farms (Dustan and Bromage, 1986). Also, similar photoperiod manipulation is the tool most used by farms to control growth, reproduction and smoltification of Atlantic salmon (Berrill et al, 2003), though the physiological mechanisms underlying such commercial manipulations are still poorly understood. Increasing awareness of the likely occurrence of endogenous rhythms in cultured fish has, however, prompted studies, for example, of flexibility in rhythms of feeding (Boujard et al, 1995).…”
Section: Chronobiology and Aquaculturementioning
confidence: 99%
“…The fish exhibited free-running circa-annual rhythms of gonadal maturation and ovulation which were self-sustaining for three circa-annual cycles. The role of photoperiodic manipulation, against the background of circa-annual and circadian periodicity, needs to be more fully evaluated as a basis for increased aquaculture yields (Berrill et al, 2003).…”
Section: Chronobiology and Aquaculturementioning
confidence: 99%